2014
DOI: 10.1016/j.jnucmat.2014.05.052
|View full text |Cite
|
Sign up to set email alerts
|

Annealing tests of in-pile irradiated oxide coated U–Mo/Al–Si dispersed nuclear fuel

Abstract: is an open access repository that collects the work of Arts et Métiers ParisTech researchers and makes it freely available over the web where possible. a b s t r a c t U-Mo/Al based nuclear fuels have been worldwide considered as a promising high density fuel for the conversion of high flux research reactors from highly enriched uranium to lower enrichment. In this paper, we present the annealing test up to 1800 °C of in-pile irradiated U-Mo/Al-Si fuel plate samples. More than 70% of the fission gases (FGs) ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Comparing the present results to those after thermal annealing on in-pile irradiated IRIS4 fuel [29], the following becomes evident:…”
Section: Atomized Uemo/al(si) Powder Fuel (Iris4)supporting
confidence: 65%
See 2 more Smart Citations
“…Comparing the present results to those after thermal annealing on in-pile irradiated IRIS4 fuel [29], the following becomes evident:…”
Section: Atomized Uemo/al(si) Powder Fuel (Iris4)supporting
confidence: 65%
“…In the following, the obtained results are compared to two exemplary in-pile irradiation tests, the RERTR6 test performed with monolithic layer systems [27] and the IRIS4 test realized with oxide-coated atomized UeMo powder dispersed in an Al(2.1wt%Si) matrix [28,29]. Additionally, the irradiation parameters for all these presented tests are listed in Table 3.…”
Section: Comparison With In-pile Irradiated Uemo Fuelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Heat of reaction measurements performed on unirradiated U-10Mo fuels dispersed in an Al matrix by Ryu et al also showed an exothermic reaction occurring around 645°C that was associated with melting of the Al matrix [20]. Similarly, annealing tests performed by Zweifel et al on irradiated U-Mo fuel dispersed in an Al-Si matrix showed a high fission gas release at 670°C [21]. While neither aforementioned study contained Zr, the exothermic reaction is primarily driven by melting of the Al alloy cladding and/or matrix (in the case of dispersion fuels).…”
Section: Discussionmentioning
confidence: 88%
“…The difference with the current system is that the Zr serves as a diffusion barrier between the Al cladding and U-Mo fuel, to prevent interaction layer formation as described in Refs. [20,21]. However, an exothermic reaction is observed following the melting of the cladding despite the presence of this diffusion barrier.…”
Section: Discussionmentioning
confidence: 99%